2022
DOI: 10.1021/acs.joc.1c02141
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Reductive Opening of Benzylidene Acetals with Dichlorophenylborane/Triethylsilane: Previously Unreported Side Reactions and How to Prevent Them

Abstract: Arylidene acetals are widely used protecting groups, because of not only the high regioselectivity of their introduction but also the possibility of performing further regioselective reductive opening in the presence of a hydride donor and an acid catalyst. In this context, the Et3SiH/PhBCl2 system presents several advantages: silanes are efficient, environmentally benign, and user-friendly hydride donors, while PhBCl2 opens the way to unique regioselectivity with regard to all other Brønsted or Lewis acids us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…To avoid this, use of only 1.1 equivalents of Et3SiH in CH2Cl2 at low temperatures has been reported. 31 Upon adopting these conditions for disaccharide 24 for 20 minutes all starting material was consumed and there was no notable side product formation by TLC analysis. Subsequent C6-O-benzoylation of the crude material delivered disaccharide 27 in 73% over two steps.…”
Section: Post Glycosylation Oxidation To Access Cs Precursor Disaccha...mentioning
confidence: 98%
See 1 more Smart Citation
“…To avoid this, use of only 1.1 equivalents of Et3SiH in CH2Cl2 at low temperatures has been reported. 31 Upon adopting these conditions for disaccharide 24 for 20 minutes all starting material was consumed and there was no notable side product formation by TLC analysis. Subsequent C6-O-benzoylation of the crude material delivered disaccharide 27 in 73% over two steps.…”
Section: Post Glycosylation Oxidation To Access Cs Precursor Disaccha...mentioning
confidence: 98%
“…However, in CH2Cl2, when an excess of Et3SiH is used, the silane reduces PhBCl2 to PhBHCl, which can hydroborate alkenes, presenting a potential problem for our anomeric O-allyl moiety. To avoid this, use of only 1.1 equivalents of Et3SiH in CH2Cl2 at low temperatures has been reported 31. Upon adopting these conditions for disaccharide 24 for 20 minutes all starting material was consumed and there was no notable side product formation by TLC analysis.…”
mentioning
confidence: 99%
“…Nevertheless, the chlorine-substituted borane 49 was detected by HRMS after electrolyzing for 45 min (Scheme A.c). We inferred that the chlorine radical might be quickly trapped by p -ethylphenylboronic acid as a reactive intermediate to avoid being consuming within the electrical double layer and then cross-coupled with carbon radical by forming dechlorinated boranes. , These observations indicated that the ATRA mechanism might be involved in the electrochemical process. No target product was observed under divided cell electrolysis, suggesting the importance of employing paired electrolysis in this process (Scheme A.d).…”
mentioning
confidence: 94%
“…Based on the above experiments and literature precedents, , a plausible mechanism for electrochemical chlorosulfonylation is proposed in Scheme C. First, sulfonyl chloride is reduced to a sulfonyl radical, which is subsequently trapped by styrene to form P1 .…”
mentioning
confidence: 98%